Evaluation of Gingival Pigmentation and Related Factors on Former Smokers - Samir Goyushov; Cihan Ateş; Süleyman Emre Meşeli (Stilus Optimus, 2024)
Objectives: Gingival pigmentation, the most common etiological factor of which is smoking, is a clinical condition that causes aesthetic complaints. Due to the dose-dependent effect of smoking, gingival pigmentation may present regression following cessation. This cross-sectional study aimed to evaluate gingival pigmentation in former tobacco consumers and compare with current ones. Material and Methods: A total of 110 people, 70 of whom were current smokers (Group CS) and 40 of whom were former smokers (Group FS), were included in the study. Participants filled out the data collection forms containing questions on demographic features and information related to tobacco consumption. In addition, all individuals were examined with Hedin's melanin index (HMI) to evaluate gingival pigmentation. Statistical significance was set at the P < 0.05 level. Results: The population consisted of 57.3% male, and the mean age of all participants was 39.43 (SD 12.3) years. The mean duration of tobacco consumption did not differ between groups, whereas the mean HMI score of Group FS was significantly lower (P = 0.001). The correlation analyses showed that while the HMI score of Group CS was in relation to both daily consumption amount and duration of consumption (for both, P < 0.01), the HMI score of Group FS showed a negative association with only time elapsed after cessation (P = 0.000). Conclusions: Considering the limitations of this study, the outcomes revealed a dose- and a time-dependent relation of gingival pigmentation in smokers. However, gingival pigmentation in former tobacco consumers was negatively correlated only with time elapsed after cessation.